Collaboration or fragmentation? Biodiversity management through the common agricultural policy. (May 2017) - Leventon, Julia; Schaal, Tamara; Velten, Sarah; Dänhardt, Juliana; Fischer, Joern; Abson, David J.; Newig, Jens
Highlights: We study how CAP facilitates landscape scale biodiversity management in three case studies. CAP hinders collaboration between farmers in a landscape by targeting individuals. CAP prevents the emergence of actors that could coordinate landscape scale collaboration. CAP fails to engage with existing barriers to farmer collaboration within landscapes. For biodiversity benefits, policy reforms should address these shortcomings. Abstract: We argue that the current system of agri-environment management in the European Common Agricultural Policy is ineffective at conserving biodiversity in part because it promotes fragmentation instead of collaboration of actors, thus hindering coordinated biodiversity management. Actor fragmentation is reinforced by the Common Agricultural Policy (CAP) in three ways: (1) through targeting individual farmers; (2) by creating confusion around coordination roles for increasing numbers of actors; and (3) by failing to engage with barriers to collaboration among farmers. Our findings draw on empirical evidence collected through multi-stakeholder workshops in Germany and Sweden. Our argument adds a different dimension to accepted explanations for the ineffectiveness of CAP for biodiversity management. Traditionally, explanations have focussed on low levels of farmer uptake of relevant measures, or the lack of ecological knowledge informing such measures. The level of actor fragmentation identified here suggests that a fundamental rethink of farmland biodiversity management is needed. We propose a new research agenda to identify more effective governance approaches.